Sand calcites as a key to Pleistocene periglacial landscapes. (May 2021) - Thiry, Médard; Innocent, Christophe; Girard, Jean-Pierre; Milnes, Anthony Richard; Franke, Christine; Guillon, Sophie
Abstract: We tested the potential for sand calcites to serve as a novel paleoclimate archive by investigating their age and formation conditions. Fontainebleau sand calcites are Pleistocene in age (based on 14 C and U-Th dating) and were primarily formed during glacial periods. δ 13 C values increase with the depth at which these sand calcites formed, consistent with open and closed CO2 systems. Interpretation of the δ 18 O-T relationship in sand calcites points primarily to their formation at a low temperature, around 2°C in shallow ground water and at about 9°C in deeper ground-water settings. Their occurrence, characteristics, and compositions suggest crystallization from paleo-ground waters in permafrost environments. Crystallization of sand calcites was triggered by degassing of cold carbonate-containing surface waters as they infiltrated warmer subsurface ground-water environments. We consider sand calcites to be important indicators of interactions between meteoric water and ground water in Pleistocene periglacial landscapes. Their disposition may point to specific features of periglacial landscapes, and their ages could permit an assessment of landscape incision rates. Large crystals and zoned spheroliths may, in fact, encapsulate continuous high-resolution records of continental glacial and periglacial paleoenvironments.